Quantitative expression analysis and study of the novel human kallikrein-related peptidase 14 gene (KLK14) in malignant and benign breast tissues - Papachristopoulou, G.; Avgeris, M.; Charlaftis, A.; Scorilas, A. (Thrombosis and Haemostasis, 2011)
Human kallikrein-related peptidase 14 gene (KLK14) is regulated by androgens and progestins. This gene is expressed in the central nervous system and endocrine tissues such as the breast, prostate and ovary. The differential KLK14 mRNA expression levels are related to several human neoplasias, among them breast cancer. The aim of this study was to analyse the KLK14 expression in breast tissues and to investigate its differential diagnostic and prognostic value in the mammary carcinomas. For this purpose, we isolated total RNA from 70 malignant and 33 benign specimens. After testing RNA quality, we synthesised cDNA by reverse transcription and applied a highly sensitive quantitative real-time PCR (qRT-PCR) method for KLK14 mRNA quantification using the SYBR Green(R) chemistry. HPRT1 was used as a reference gene and the BT20 breast cancer cell line as a calibrator. Relative quantification analysis was performed using the comparative CT method 2-DeltaDeltaCT. KLK14 expression was detected in both types of breast tumours. However, a statistically significant increase of the KLK14 mRNA level was observed in the malignant, compared to the benign tumour samples (p<0.001), highlighting its value in discriminating these breast lesions. Elevated KLK14 expression profiles were associated with higher tumour grade (p=0.043) and size (p=0.007) in cancerous samples. Furthermore, KLK14 mRNA expression showed negative correlation in a statistically significant manner with estrogen receptor status (p=0.024). In accordance with logistic regression models (p=0.012) and receiver-operating-characteristics analysis (p<0.001), KLK14 gene expression could be evaluated as a putative independent diagnostic biomarker in breast tumour biopsies.
Keywords: Biomarkers, Tumor/*analysis; Biopsy; Breast Neoplasms/*diagnosis; DNA, Complementary; Female; Humans; Kallikreins/*analysis; Logistic Models; Neoplasm Proteins/analysis; Receptors, Estrogen/analysis; RNA, Messenger/analysis; ROC Curve